Mapping Regional Well-Being in the Universal Health Coverage System in Taiwan - Wang F; Weng H (Dove Medical Press, 2020)
Fuhmei Wang,1 Haolun Weng2 1Department of Economics in College of Social Science and Department of Public Health in College of Medicine, National Cheng Kung University, Tainan, Taiwan; 2Department of Economics, National Cheng Kung University, Tainan, TaiwanCorrespondence: Fuhmei WangDepartment of Economics in College of Social Science and Department of Public Health in College of Medicine, National Cheng Kung University, Tainan, TaiwanEmail fmwang@mail.ncku.edu.twPurpose: Regarding the universal health coverage (UHC) goal of eliminating health disparity, this study seeks to examine whether this objective has actually been achieved and whether residence affects health and well-being inequality.Methods: Based on Taiwan’s experience with its UHC system, this research quantifies health and well-being indicators, including quality-adjusted life expectancy (QALE), consumption, and utility-adjusted life expectancy (UALE), and uses the geographic information system (GIS) to map regional well-being throughout Taiwan. Using spatial lag regressions, this study estimates how residence and socio-economic factors affect population’s well-being.Results: Estimation results indicate a 1‰ increase in the mortality rate reduces the population’s UALE by 0.4131 utility-adjusted life-years (UALYs). The differences in health and well-being indicators between urban and rural residents were 6.49 quality-adjusted life-years (QALYs) and 3.84 UALYs. Residents living in Taipei City had the highest level of QALE, consumption, and well-being, and those in Taitung County had the lowest level of QALE and well-being. The regional spatial autocorrelation results show that a population’s health status and well-being are connected to residence.Conclusion: Our estimation results show that risk of higher mortality rates in disadvantaged areas appears to be associated with well-being inequality, even with universal healthcare coverage. We suspect that related health intervention efforts, such as preventive and curative medical devotion, in Taiwan might not have effectively reached more rural residents, and thus recommend more work be undertaken to reduce mortality rates in these communities.Keywords: quality of life, utility-adjusted life expectancy, universal health coverage